Strategic Planning Research: Toward a Theory-Driven Agenda - Wolf, Carola; Floyd, Steven W. (Journal of Management, 2017)
This review incorporates strategic planning research conducted over more than 30 years and ranges from the classical model of strategic planning to recent empirical work on intermediate outcomes, such as the reduction of managers’ position bias and the coordination of subunit activity. Prior reviews have not had the benefit of more socialized perspectives that developed in response to Mintzberg’s critique of planning, including research on planned emergence and strategy-as-practice approaches. To stimulate a resurgence of research interest on strategic planning, this review therefore draws on a diverse body of theory beyond the rational design and contingency approaches that characterized research in this domain until the mid-1990s. We develop a broad conceptualization of strategic planning and identify future research opportunities for improving our understanding of how strategic planning influences organizational outcomes. Our framework incorporates the role of strategic planning practitioners; the underlying routines, norms, and procedures of strategic planning (practices); and the concrete activities of planners (praxis).